Covid-19 impact on technology usage: An empirical evidence from Indonesia zakat institutions - Mubarak, Darihan; Mohd Shafiai, Muhammad Hakimi; Wahid, Hairunnizam; Anuar, Aimi (Asian Journal of Islamic Management (AJIM), 2022)
Purpose − The study aims to determine what factors influence the use of technology in zakat institutions in Indonesia using the Technological, Organizational, Environmental (TOE) model.Methodology − This research is based on a quantitative online survey of 125 amils at zakat institutions in Indonesia. The sample consisted of 55% men and 45% women. Data were analyzed using SPSS 26 and PLS-SEM to test variables and hypotheses.Findings − The results showed that organizational readiness and external pressure have a significant positive impact on the use of technology in zakat institutions. Interestingly, Information Technology (IT) infrastructure and interoperability do not significantly affect technology usage because technology users want it to be easy-to-understand and easy-to-use. Thus, an easy-to-understand and easy-to-use technology give an excellent opportunity to achieve the zakat institution's goals.Originality − This study is one of the first to examine the impact of the variables in the TOE Model on technology usage in Indonesian zakat institutions during the COVID-19 pandemic. Research limitations − This study was conducted using cross-sectional data, which has limitations in explaining the relationship between variables that are likely to change over time. In addition, some respondents were not familiar with the proposed questionnaire. Lack of understanding may cause respondents to answer questions improperly.Practical implications − The results are essential for all stakeholders of zakat institutions, especially policymakers, to increase the use of technology to affect the performance of zakat institutions in the context of the realization of zakat, infaq, sadaqah (ZIS) collection in Indonesia.